2010
DOI: 10.3109/09513591003649815
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of adding peripheral neuromodulation (stoller afferent neuro-stimulation) to anti-muscarinic therapy in women with severe overactive bladder

Abstract: Combining SANS and anti-muscarinic therapy resulted in significantly better clinical outcomes and IIQ-7 scores as compared with anti-muscarinic treatment alone in patients with severe overactive bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
2
21
0
1
Order By: Relevance
“…In comparison of PTNS and multimodal therapy, there was significant difference of symptoms episodes favouring multimodal therapy in a study by Sancaktar et al 40 and significantly higher response rate of multimodal therapy group compared to PTNS reported by Karademir et al 31 In the treatment of neurogenic OAB specifically, PTNS showed similar results. Kabay et al 41 evaluated 32 patients with Parkinson's disease accompanied with neurogenic detrusor DO.…”
Section: Efficacysupporting
confidence: 71%
“…In comparison of PTNS and multimodal therapy, there was significant difference of symptoms episodes favouring multimodal therapy in a study by Sancaktar et al 40 and significantly higher response rate of multimodal therapy group compared to PTNS reported by Karademir et al 31 In the treatment of neurogenic OAB specifically, PTNS showed similar results. Kabay et al 41 evaluated 32 patients with Parkinson's disease accompanied with neurogenic detrusor DO.…”
Section: Efficacysupporting
confidence: 71%
“…In other RCTs, superiority of PTNS over placebo, and bladder training and PFMT was reported. Combination of PTNS plus antimuscarinics resulted in significantly better outcomes as compared with antimuscarinics alone . In a systematic review, four RCTs met their criteria for good quality .…”
Section: Types Of Neuromodulation (Table )mentioning
confidence: 99%
“…Percutaneous tibial nerve stimulation ( PTNS ) delivers neuromodulation to the pelvic floor through the S2‐4 junction of the sacral nerve plexus via the less invasive route of the posterior tibial nerve . Using the fine needle electrode insertion above the ankle, the tibial nerve is accessed.…”
Section: Types Of Neuromodulation (Table )mentioning
confidence: 99%
“…Six randomized trials provided data on the use of tibial nerve stimulation for treatment of urge urinary incontinence (39)(40)(41)(42)(43)(44). These trials included a total of 426 women, Peters et al had the largest sample analyzing 174 women (39).…”
Section: Tibial Nerve Electrical Stimulationmentioning
confidence: 99%
“…Three trials compared IVES and anticholinergic drugs (41)(42)(43). All reported significant improvement related to baseline in both groups, nevertheless, two of them found significant improvement PTNS group related to medication.…”
Section: Tibial Nerve Electrical Stimulationmentioning
confidence: 99%